2012
DOI: 10.1192/pb.bp.111.034413
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry recruited you, but will it retain you? Survey of trainees' opinions

Abstract: Aims and methodTo gather opinion from trainees across England about their current experiences and future career plans. This was done via an internet-based survey.ResultsOut of the 359 responses we received, 65.8% of trainees planned to stay in psychiatry until retirement. Trainees felt several issues were problematic, including the attitude of other specialties towards psychiatry, perceived substandard treatment of psychiatric patients by other specialties and implications of New Ways of Working.Clinical impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Barras & Harris 38 explored trainee's experiences ( n = 359) within psychiatry. Trainee attitudes were grouped into different categories.…”
Section: Resultsmentioning
confidence: 99%
“…Barras & Harris 38 explored trainee's experiences ( n = 359) within psychiatry. Trainee attitudes were grouped into different categories.…”
Section: Resultsmentioning
confidence: 99%
“…The erosion of the role of the psychiatrist has also been cited by some psychiatry trainees as a potential factor that would make them consider leaving psychiatry training. 21 The flattened hierarchy compared with other clinical specialties such as surgery, cardiology and general practice may deter other students whose primary ambition is to be a 'doctor' who is a 'leader' in the traditional sense, and they may take note of the increasing status difference between modern consultant psychiatrists and their counterparts in other disciplines.…”
Section: The Weakening Medical Identitymentioning
confidence: 99%
“…Because the present study is a cross-sectional interview scheme, it cannot be confirmed whether or not job satisfaction truly does increase with increasing seniority. Increasing satisfaction with increasing seniority has however also been suggested in other published trainee surveys [7,16]. Interestingly, the 2011 National Trainee Survey of UK core psychiatry trainees similarly demonstrates an upward trend in trainee satisfaction rates from CT1 to CT3 year, with a higher satisfaction rate in CT3 trainees as compared to CT1 trainees [16].…”
Section: Discussionmentioning
confidence: 65%
“…Many wards seemed to be operating with what might be described as a ‘siege mentality’, with high levels of violence and disturbance, combined with a culture of demoralisation and the sense that both medical staff and nursing staff were feeling impotent, overwhelmed and unable to change the situation. These factors have been previously shown to be associated with high dissatisfaction rates from psychiatry trainees and contributing to decisions to leaving psychiatry [3,4,7]. The authors are not aware of any evidence of educational value in the ‘baptism of fire’ experienced by trainees exposed to such environments and the concept of learning by being ‘thrown in at the deep end’.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation